CEGAH BULLYING MELALUI PROGRAM ANYAMAN (AMAN, NYAMAN, DAN MENYENANGKAN) - Humaira - Humaira; Reply Ahmad Akbar; Kamarudin Kamarudin; Ainun Zamirah; Julianti Julianti; Sulandaniallamiah Sulandaniallamiah (Universitas Muhammadiyah Mataram, 2025)
MTS Sa'adatul Ikhwan NW Rensing is one of the oldest/first private schools in Rensing Village, West Sakra District, East Lombok Regency, where the majority of students are Lomboknese, to make efforts to prevent bullying in the school environment, the PLP 2 INTEGRATED KKN-DIK team, Universitas Muhammadiyah Mataram carries out outreach by focusing on providing literacy about bullying. The method used is socialization and joint mentoring to make efforts to prevent bullying in the Mts school environment. Sa'adatul Ikhwan NW Rensing. The result of this activity was that we received a positive response from the teachers of Mts Sa'adatul Ikhwan NW Rensing and the students were very enthusiastic about the outreach activities that we carried out. This can be seen from the efforts to prevent bullying through the JAVA (Safe, Comfortable and Fun) school program. In this activity, the PLP 2 INTEGRATED KKN-DIK team agreed to make efforts to prevent bullying through the YANGAMAN (Safe, Safe, and Fun) school program. Comfortable, and fun) for Mts Sa'adatul Ikhwan NW Rensing students as an effort to reduce bullying prevention measures in the MTS Sa’adatul Ikhwan NW Rensing school environment.